PROGRAM PEMBIASAAN DALAM MENGUCAPKAN SALAM PADA ANAK TAMAN KANAK KANAK - achmadi achmadi (incrementapedia, 2019)
The habituation program is an icon of learning and forming good behavior for Early Childhood. The process ofperforming to behave good attitudes is given to early childhood by applying of norms in the society. Forexample "The greeting". should have been able to do for the children who have 5-6 years old, but there are stillsome children who have not been able to do it. Another example there are still some children who do not wantto say hello when they are meeting their friends or other people. Based from these problems, the researcherswant to try to overcome them through habituation programs by using audiovisual media. The goal of this studyis to improve the children's performance to apply well greetings when they are meeting to their friends or toother people. The meaning of well greeting is: The children can say greetings correctly, and want to say hellowhen they meet to their friends or to other people. The solution of the problem is: Does the habituation programby seeing of some greeting example in the Audiovisual media can influence to the greeting’s acivement for earlychildhood? The author uses quantitative research by quasi-experimental with types of treatment by subject onegroup design. The pattern of this research is: Pre test – Action of Experiment - Post test. The data collection isused by the performance tests and the observations. The Implementation is The children are asked to say helloand tobe observed when they meet with their friends or with other people. The data analysis uses the statisticalanalysis with the t-test. The results of the study showed that learning with audiovisual impressions of wellbehaviorwasveryeffectiveforearlychildhood.Becauseitcanattracttheattentionofchildren,thematerialis easily understood or meaningful for children, and makes some children more active both physically andpsychologically. Another reason that audiovisual media has characteristics: can be seen, can be imitated, canbe felt, and can be heard, so it is very effective in improving habituation programs for early childhood.